Menelisik 'Greenwashing’ di Balik Gembar-Gembor ESG: Studi Kasus Persepsi dan Pengalaman Investor Ritel terhadap Implementasi Praktik ESG Perusahaan di Indonesia Pasca Regulasi Terbaru - Yehezkiel Benaya Nanlohi; Marcell Willard Susanto; Dicky Satria Ananta Haqq; Indrian Arsya Nandito; Titiek Rachmawati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this research is to analyze Indonesian retail investors' perceptions of ESG implementation post the latest regulations, their experiences in detecting greenwashing, and the factors influencing these aspects. The research employed a qualitative approach using online data such as sustainability reports, news, surveys, and forums. The results indicate that retail investors' understanding of ESG varies, with a relatively low level of trust in corporate claims due to concerns about greenwashing. They rely on diverse information sources and use subjective ESG assessment criteria. Investors' experiences in identifying potential greenwashing are marked by the discovery of inconsistent information and suspicion towards specific indicators; however, actions taken vary and are often hindered by limitations. These perceptions and experiences are influenced by investor characteristics, the quality of information sources, regulatory effectiveness, corporate communication practices, and social and media influence. This research concludes the necessity for enhanced ESG literacy, reporting standardization, stricter oversight, and transparent communication to build trust and promote sustainable investment in Indonesia.